Agritourism and direct sales clusters in the United States. (April 2023) - Schmidt, Claudia; Tian, Zheng; Goetz, Stephan J.; Hollas, Chadley R.; Chase, Lisa
Abstract: Agritourism and direct-to-consumer sales are increasingly used as diversification strategies to generate additional farm revenue streams. Yet despite their growing importance, the impacts, interactions, and adoption of these strategies remain poorly understood. Here we use univariate and bivariate local Moran's I statistics to identify agritourism and direct-to-consumer sales hotspots in the United States and a Seemingly-Unrelated-Regression Spatial Durbin Model to examine the association between agritourism and direct farm sales to consumers. We find that agritourism and direct sales reinforce each other within the same county but not consistently across neighboring counties.